Prevalence And Factors That Contributing of Baby Blues Syndrome On Postpartum Mothers - Ekadewi Retnosari; Siti Fatimah (Yayasan Rumah Ilmu Professor, 2022)
Baby Blues syndrome describes different groups of depressive symptoms that can occur during the first 6 weeks after birth. The postpartum period is the critical time during which mild and severe mood disorders can occur. Understanding the prevalence and related factors of Baby Blues Syndrome becomes mandatory for early detection and treatment. The institution-based cross-sectional study was conducted from May 1 to June 30, 2021. Study participants were qualified women who visited hospitals and health centers in Muara Enim, Indonesia for postpartum care. The Edinburgh postnatal depression scale was used to assess ba by blues syndrome. A systematic random sampling technique was used to collect the data, then coded instatistical tests with spss application version 24. Bivariate and multivariate binary logistic regressions are performed to decipher related factors. A total of 208 mothers who visited postpartum care were respondents, where the response obtained was 100% of the expected target. The prevalence of Baby Blues Syndrome was found at 15.6% (95%CI = 11.7, 19.8). Several factors were found to be the baby blues sidrome i.e. single parents, poor social support, having a child currently hospitalized, and a history of family members or close relatives who died significantly associated with. The prevalence of sindrome baby blues is quite high in postpartum mothers from the results of several studies at various points of location. Major events and life traumas are associated with an increased risk of postpartum depression that gave rise to Baby Blues Syndrome. Health care providers should be aware of the state of the mother during the puerperium, they must provide support from the beginning of pregnancy to reduce the risk of depression in the postpartum period. Health care professionals working in postpartum care clinics should pay special attention to mothers who are single parents, have poor social support, have children hospitalized at this time, and experience the death of family members or close relatives.